História da educação agrícola do sul de Minas Gerais : a Escola Agrícola de Muzambinho (1948-1985) - Vieira, Lívia Carolina (2016)
This research lies in the field of history of school institutions and has as its object of study the Agricultural School of Muzambinho, with the objective of analyzing the process of is creation and the formation offered to students. This study also assists in the understanding of the goals and directions of the institutions of agricultural education in Southern Minas Gerais, important region for agricultural production in the time frame chosen for the analysis: 1948 to 1985.The choice of the period has since the early initiatives for school creation until the end of the period of military dictatorship in Brazil to analyze the implementation of the model school - farm, a result of the relations between the United States and Brazil. The primary documents were the main basis of research, among them the reports of management; student identification cards; enrollment maps; academic contents lists; school subjects lists and table of content; letters with requests from students and teachers to the school secretary; newspapers; laws and decrees relating to the period, opinions, resolutions, messages of the governors, reports of the President of the Province; pictures of the school and the city. Were also carried out interviews with former students and school personnel. The method chosen to make such analyzes is dialectical and historical materialism, which investigates the intimate connection between the way in which society produces its material existence and the school institution that creates. As a reference we chose authors who investigate the history of school institutions as Magalhães (1998), Saviani (2007), Araújo (2007) (2000) and Buffa; Nosela (2013). The results indicated the connection of the school with the need for training of rural workers and the modernization of the field, driven by the influence of the United States after 1960. These actions promote changes in national production and the agricultural education based on the implementation of the school-farm model.